2003
DOI: 10.1093/ajcn/78.5.1030
|View full text |Cite
|
Sign up to set email alerts
|

Pathways: a school-based, randomized controlled trial for the prevention of obesity in American Indian schoolchildren

Abstract: These results document the feasibility of implementing a multicomponent program for obesity prevention in elementary schools serving American Indian communities. The program produced significant positive changes in fat intake and in food- and health-related knowledge and behaviors. More intense or longer interventions may be needed to significantly reduce adiposity in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
530
1
22

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(564 citation statements)
references
References 34 publications
11
530
1
22
Order By: Relevance
“…The current review includes Caballero's study on American Indian schoolchildren. 17 Epstein studied children of obese parents and compared two strategies, one that increased fruit and vegetable intake and the other that decreased fat and sugar intake. 18 One of the studies by Alexandrov 7 included, to some extent, a high-risk strategy, since boys with multiple risk factors for cardiovascular disease received more intensive preventive intervention than the others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current review includes Caballero's study on American Indian schoolchildren. 17 Epstein studied children of obese parents and compared two strategies, one that increased fruit and vegetable intake and the other that decreased fat and sugar intake. 18 One of the studies by Alexandrov 7 included, to some extent, a high-risk strategy, since boys with multiple risk factors for cardiovascular disease received more intensive preventive intervention than the others.…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies have reported any harmful effects, which is encouraging for future plans and projects. 17,20 Publication bias One could ask whether publication bias might be responsible for the distribution of positive and neutral studies and the lack of negative findings. However, a large number of studies have been included, many of which did not present positive results, but were published nevertheless.…”
Section: Risks Of Preventive Interventionsmentioning
confidence: 99%
“…It should include appropriate indicators of body fatness according to age, sex and ethnicity of the group 30,33 .…”
Section: Prevention Of Overweightmentioning
confidence: 99%
“…On the other hand, programmes of low 'certainty of effectiveness' and high 'potential for population impact' (e.g. the Pathways schools intervention programme from the USA that had positive qualitative results on reach, uptake and programme logic Gittelsohn et al 1999) but lack of hard positive outcomes (Caballero et al 2003)) could also be rated as promising.…”
Section: Promising Programmesmentioning
confidence: 99%